Onto-fenomenologia do nascimento: questões sobre a gênese da subjetividade - Souto, Symon Sales (2023)
The aim of our thesis is to present an onto-phenomenology of birth based on Michel Henry's thought, which will be developed from two moments. In the first instance, we propose to approach the correlated relationship between Life and the living based on Michel Henry's final writings in an attempt to understand what the human is in this abyssal correlation. Our concern goes back to the original impression of being in the materiality of its self-impression. Our question aims to understand how the paradox between singularisation and totalisation can be dissolved through a radical re-reading of Being and its way of revealing itself immanently. Thus, our thesis deals with the place and role of human reality in the question of Being's unveiling of itself. To this end, in a second moment, we must recognise that our author's final trilogy should not be read as a nolens volens theology, but as a continuation of his own preliminary phenomenological considerations, since les derniers oeuvres presents us with the ontological, structural and fundamental determination of the original essence of living, that is, the only way for Life to become life. In this sense, we will see that our author's phenomenology, in opposing monism, presents us a new theory about the human condition, not through a genealogy of the world, but through a genealogy of Life. For this purpose, we will map the contours and essential elements of this meaning from C’est moi la vérité: pour une philosophie du christianisme (1996), Incarnation (2000) and Paroles du Christ 2002).